Practising evidence-based medicine (EBM): a descriptive analysis of medical students' whole-task EBM assignments. Issue 2 (6th February 2017) - Maggio, Lauren A; Capdarest-Arest, Nicole
Abstract : Researchers have suggested whole-task learning activities to practice and teach evidence-based medicine (EBM); however, limited description exists of their use in EBM curricula. This article describes medical students' execution of a whole-task EBM assignment and characterises themes emerging from assignment submissions. Between 2013 and 2015, Stanford University's paediatric clerkship students completed a whole-task EBM assignment based on a patient encounter. The assignment captured students' efforts to perform all EBM steps and describe their patient scenario and future knowledge needs strategies. Assignments were analysed using descriptive statistics and qualitative description. 123 students completed the assignment. Students formulated therapy (n=76), prognosis (n=18), diagnosis (n=15), harm (n=9) and aetiology (n=2) questions, and used a single (n=58) or multiple information resources (n=57). Based on evidence appraisal, 95 students indicated that the found evidence would inform future practice while 16 were sceptical of its conclusivity. 65 learners wanted to share evidence with colleagues; 33 with patients and families. To meet future knowledge needs, learners suggested using a structured approach (eg, PICO (patient, intervention, comparison and outcome); n=58), reading more primary literature (n=22) and creating question logs (n=21). This article provides a glimpse into students' EBM process and demonstrates the feasibility of whole-task activities for use in EBM training. Findings related to students' clinical uncertainty and information sharing raise questions about coverage of these topics in current EBM training and suggest that further investigation is warranted.